Long-term Outcomes in Juvenile Myositis Patients - Tsaltskan, Vladislav (Semin Arthritis Rheum, 2019)
OBJECTIVE: Juvenile idiopathic inflammatory myopathies (JIIM) are rare, chronic autoimmune muscle diseases of childhood, with the potential for significant morbidity. Data on long-term outcomes is limited. In this study we investigate correlations between clinical and demographic features with long-term outcomes in a referral population of adult patients with JIIM. METHODS: Forty-nine adults with JIIM were assessed at two referral centers between 1994 and 2016. Features of active disease and damage at a cross-sectional assessment were obtained. Regression modeling was used to examine factors associated with long-term outcomes, defined by the presence of calcinosis or a higher adjusted Myositis Damage Index (MDI) score. A multivariable model of MDI was constructed using factors that were statistically significant in bivariate models. RESULTS: At a median of 11.5 [IQR 4.5-18.9] years following diagnosis, median American College of Rheumatology (ACR) functional class was 2 [1.5-3.0], Health Assessment Questionnaire (HAQ) score was 0.4 out of 3.0 [0.0-1.0], and manual muscle testing (MMT) score was 229 out of 260 [212.6-256.8]. Median MDI score was 6.0 [3.5-8.9], with the most commonly damaged organ systems being cutaneous and musculoskeletal. Factors associated with an elevated MDI score were the presence of erythroderma and other cutaneous manifestations, disease duration, and ACR functional class. Calcinosis was present in 55% of patients. The strongest predictors of calcinosis were disease duration, periungual capillary changes, and younger age at diagnosis. CONCLUSION: In a tertiary referral population, long-term functional outcomes of JIIM are generally favorable, with HAQ scores indicative of mild disability. Although most patients had mild disease activity and virtually all had significant disease damage, severe or systemic damage was rare. Certain clinical features are associated with long-term damage and calcinosis.